Electronic versus steric effects of pyridinophane ligands on Pd(iii) complexes. Issue 4 (22nd December 2017) - Tang, Fengzhi; Park, Sungho V.; Rath, Nigam P.; Mirica, Liviu M.
Abstract : Reported herein is the study of the electronic and steric effects of pyridinophane ligands on the corresponding Pd(iii ) complexes. Abstract : Several new Pd II and Pd III complexes supported by electronically and sterically tuned tetradentate pyridinophane ligands Me N4 OMe, Me N4, and t Bu N4 were isolated and fully characterized ( Me N4 OMe : N, N ′-dimethyl-2, 11-diaza[3, 3](2, 6)- para -methoxypyridinophane; Me N4: N, N ′-dimethyl-2, 11-diaza[3, 3](2, 6)pyridinophane; t Bu N4: N, N ′-di- tert -butyl-2, 11-diaza[3, 3](2, 6)pyridinophane). Cyclic voltammetry studies, UV-vis and EPR spectroscopy, and X-ray crystallography were employed to reveal that the steric properties of the N -substituents of the R N4 ligands have a pronounced effect on the electronic properties of the corresponding Pd III complexes, while the electronic tuning of the ligand pyridyl groups has a surprisingly minimal effect. An explanation for these observations was provided by DFT and TD-DFT calculations which suggest that the electronic properties of the Pd III complexes are mainly dictated by their frontier molecular orbitals that have major atomic contributions from the Pd center (mainly the Pd d z 2 atomic orbital) and the axial N atom donors.